Analysis of a hybrid TATA box binding protein originating from mesophilic and thermophilic donor organisms. Issue 3 (2010) - Kopitz Kopitz, Annette Annette; Soppa Soppa, Jörg Jörg; Hauser Hauser, Karin Karin
Abstract : The TATA Box Binding Protein (TBP) is a 20 kD protein that is essential and universally conserved in eucarya and archaea. Especially among archaea, organisms can be found that live below 0°C as well as organisms that grow above 100°C. The archaeal TBPs show a high sequence identity and a similar structure consisting of α-helices and β -sheets that are arranged in a saddle-shape 2-symmetric fold. In previous studies, we have characterized the thermal stability of thermophilic and mesophilic archaeal TBPs by infrared spectroscopy and showed the correlation between the transition temperature ( T m) and the optimal growth temperature (OGT) of the respective donor organism. In this study, a "new" mutant TBP has been constructed, produced, purified and analyzed for a deeper understanding of the molecular mechanisms of thermoadaptation. The β -sheet part of the mutant consists of the TBP from Methanothermobacter thermoautotrophicus (OGT 65°C, MtTBP65) whose α-helices have been exchanged by those of Methanosarcina mazei (OGT 37°C, MmTBP37). The Hybrid-TBP irreversibly aggregates after thermal unfolding just like MmTBP37 and MtTBP65, but the T m lies between that of MmTBP37 and MtTBP65 indicating that the interaction between the α-helical and β -sheet part of the TBP is crucial for the thermal stability. The temperature stability is probably encoded in the variable α-helices that interact with the highly conserved and DNA binding β -sheets.